Karakteristik luka pada pengendara motor korban meninggal akibat kecelakaan lalu lintas yang terpapar alkohol di Yogyakarta tahun 2015-2019 - Priyambodo, Dewanto Yusuf; Yumna, Isna Izzati; Artanti, Martiana Suciningtyas Tri; Widagdo, Hendro (Jurnal Kedokteran Universitas Palangka Raya, 2024)
High alcohol consumption in Indonesia results in increasing traffic accidents yearly. Motorbike riders and results in various degrees of injuries and result to death. This study aims to determine the differences of injuries patterns in death victims as a result of traffic accidents caused by alcohol consumption and non-consumption of alcohol among motorbike riders. This research is descriptive with secondary data from visum et repertum of traffic accident fatalities in 2015-2019 at the Forensic Medicine Installation at Dr. RSUP. Sardjito. Subjects were categorized as alcohol and non-alcohol drinkers. There were 144 cases of death among motorcyclists with 114 non-alcoholic and 30 alcoholic cases with gender, age, worker status, also number, location and pattern of injuries. It can be concluded that the victims were predominantly adult men (18-65 years). The body locations most frequently injured are the head and extremities. The wound most often experienced by victims is the vulnus excoriatum.   Keywords: Traffic accidents, death, alcohol, influence of alcohol, description